Experimental infection of squirrel monkeys with nipah virus - Marianneau, P.; Guillaume, V.; Wong, K.T.; Badmanathan, M.; Looi, R.Y.; Murri, S.; Loth, P.; Tordo, N.; Wild, T.F.; Horvat, B.; Contamin, H. (Centers Disease Control, 2010)
We infected squirrel monkeys (Saimiri sciureus) with Nipah virus to determine the monkeys' suitability for use as primate models in preclinical testing of preventive and therapeutic treatments. Infection of squirrel monkeys through intravenous infection was followed by high death rates associated with acute neurologic and respiratory illness and viral RNA and antigen production.